2010
DOI: 10.1002/clc.20827
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Actigraphic and Subjective Measures of Sleep in Implantable Cardioverter Defibrillator and Coronary Artery Disease Patients

Abstract: Background:Cardiac patients frequently have insomnia symptoms that may pose risk for future cardiac events. Poor sleep relates to hyperarousal, anxiety and depression, and the incidence of hypertension and myocardial infarction.Hypothesis:The authors hypothesized that implantable cardioverter defibrillator (ICD) patients would have poorer sleep than coronary artery disease (CAD) patients related to hypervigilance for device functioning and shock discharge.Methods:Authors investigated sleep efficiency and sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
2
10
2
Order By: Relevance
“…The prevalence rate of OSA in our sample (40.5%) is consistent with previous findings in the literature (40–77%; Fries et al, 1999; Grimm et al, 2013; Mehra et al, 2006; Serizawa et al, 2008; Tomaello et al, 2010), although our rate of OSA and comorbid insomnia (11.9%) is low relative to previously reports in ICD patients with nocturnal ventricular arrhythmias (22–54.9%; Al-Jawder & Bahammam, 2011). Our prevalence rate for insomnia within the sample (28.6%) is lower but somewhat comparable to previous findings in heart failure patients (44%; Taylor et al, 2007), and suggests that insomnia is a considerable problem with these patients as a less-recognized and/or treated condition that until recently has received little attention (Cross et al, 2010). …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The prevalence rate of OSA in our sample (40.5%) is consistent with previous findings in the literature (40–77%; Fries et al, 1999; Grimm et al, 2013; Mehra et al, 2006; Serizawa et al, 2008; Tomaello et al, 2010), although our rate of OSA and comorbid insomnia (11.9%) is low relative to previously reports in ICD patients with nocturnal ventricular arrhythmias (22–54.9%; Al-Jawder & Bahammam, 2011). Our prevalence rate for insomnia within the sample (28.6%) is lower but somewhat comparable to previous findings in heart failure patients (44%; Taylor et al, 2007), and suggests that insomnia is a considerable problem with these patients as a less-recognized and/or treated condition that until recently has received little attention (Cross et al, 2010). …”
Section: Discussionsupporting
confidence: 84%
“…Only one such study, performed by Cross, McCrae, Smith, Conti and Sears (2010), has looked at the prevalence of diagnosable insomnia in this population. That study found that ICD patients reported mean sleep onset latencies (33.8 min) and wake times after sleep onset (32.6 min) consistent with empirically-validated quantitative criteria for diagnosing insomnia (K.…”
mentioning
confidence: 99%
“…41 , 42 Patients with implantable cardioverter-defi brillator (ICD) devices also show clinically signifi cant levels of sleep disruption. 34 Patients with ICDs are at an increased risk for clinically signifi cant anxiety, which is related to hypervigilance, shock anxiety, and fear of device malfunction, 34 , 43 , 44 placing these patients at increased risk for insomnia.…”
Section: Hypertension and Cardiovascular Diseasementioning
confidence: 99%
“…For example, among patients with ICDs, concerns about receiving a shock in the middle of the night may lead to increased emotional and physiologic arousal, which can interfere with sleep. 34 …”
Section: Tailoring Cbtimentioning
confidence: 99%
“…Sleep‐disordered breathing has also been related to ICD shock 20,21 . Even though sleep problems are found more frequently in cardiac patients with coronary heart disease than in patients with an ICD, 22 sleep remains an important and little studied area of concern.…”
Section: Introductionmentioning
confidence: 99%